A Rare Case of Crigler-Najjar Syndrome Type 2 - Shrestha, Anil Kumar; Sherpa, Sangay Chultim; Karki, Asmita; Agrawal, Sumit; Paudel, Deepak Raj (Journal of Nepal Health Research Council, 2025)
Crigler–Najjar Syndrome Type 2 (CNS2) is a rare autosomal recessive disorder characterized by unconjugated hyperbilirubinemia due to partial deficiency of the enzyme uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1). We present a case of a 13-month-old male admitted to Kanti Children’s Hospital with persistent jaundice since birth. Diagnostic evaluation accompanied by gene sequencing confirmed CNS2 and the patient was effectively managed with orally administered phenobarbitone. CNS2 can be distinguished from other potential causes of unconjugated hyperbilirubinemia based on bilirubin concentration and the affected patient’s response to phenobarbitone. Genetic counselling is essential for the recognition and prevention of severe hyperbilirubinemia which, in the absence of timely medical intervention, may lead to neurotoxicity. Keywords: Case report; crigler-Najjar syndrome; genetic counseling; phenobarbitone; unconjugated hyperbilirubinemia.